Peran Fintech dalam Mendorong Transaksi Berkelanjutan dan Investasi Hijau Global - Lutfiatun Qoriah; Ira Safitri; Layla Husna Nur Chifdzi; Latifatun Nisak; Pungky Lela Saputri (Lembaga Pengembangan Kinerja Dosen, 2025)
Fintech has emerged as a key driving force in fostering sustainable transactions and green investments at the global level. Through product and service innovation, fintech is making access to sustainable financial products easier, encouraging wider participation in the green economy. The role of fintech in driving global sustainable transactions and green investments is increasingly significant as the need for environmentally friendly financial solutions grows. Financial technology (fintech) facilitates wider access to green finance through inclusive and efficient digital platforms. Fintech contributes to carbon footprint reduction by adopting digital-based technologies to replace traditional resource-intensive financial processes. In addition, fintech also encourages green investment by providing services such as crowdlending for renewable energy projects, green asset tokenisation, and sustainability-based portfolio monitoring applications. Collaboration between fintech, regulators, and the traditional financial sector is key in creating an ecosystem that supports the transition to a low-carbon economy. This article discusses the strategic role of fintech in driving sustainable transactions and global green investments, the challenges faced, as well as the future potential to achieve sustainable development goals (SDGs).